SELF-CARE OF USERS WITH DIABETES MELLITUS ENTERED INTO A PROGRAM OF CAPILLARY BLOOD GLUCOSE SELF-MONITORING. - de Oliveira de Pimentel, Juliana; dos Santos, Ivânia Maria; Barreto Neto, Augusto César; Patriota de Souza, Valesca (Revista de Pesquisa: Cuidado é Fundamental)
Objective: To evaluate the performance of self-care activities of users with diabetes mellitus entered into a program of capillary blood glucose self-monitoring at home. Method: cross-sectional study, descriptive, with a quantitative approach, held at the domicile of users with diabetes mellitus that perform capillary blood glucose self-monitoring, totaling a sample of 279 users. In the evaluation of the activities of self-care Questionnaire was used of Self-care activities with Diabetes, and to collect demographic and clinical data was applied a systematic roadmap. Results: the data revealed that the specific power supply dimensions, physical activity and monitoring Glycemic demonstrates behavior of self-care is not desirable, while drug membership presented the best self-care behavior desirable. Conclusion: users with diabetes mellitus that perform capillary blood glucose self-monitoring at home require a specific accompaniment, plus continuous educational practices that foster the effective participation in the activities of self-care.